Analysis of an Elevated INTZ Water Tank under Different Wind Speed Using Analysis Tool - Ujjwal Bisen; Rahul Kumar Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2025)
Intze water tanks, characterized by their cylindrical shape and elevated position, have emerged as a prominent solution for efficient water storage and distribution. These structures offer several advantages, including optimized water capacity within a limited footprint, consistent water pressure delivery to consumers, and reduced maintenance requirements due to their smooth interior surfaces. In this research work, we have considered three similar INTZ (Intez) water tanks and designed them under different basic wind speeds and different seismic zones.
Keywords: Intze water tank; wind pressure; earthquake pressure; hydraulic pressure; joint displacement; bending moment; shear force